KELAYAKAN DAN STRATEGI PENGEMBANGAN LUMBUNG PANGAN MASYARAKAT UNTUK MENDUKUNG KETAHANAN PANGAN (STUDI KASUS PADA LPM GAPOKTAN NGUDI TANI) - Neni Irawati; Irene Kartika Eka Wijayanti; Lilik Kartika Sari (Fakultas Pertanian Universitas Janabadra, 2025)
National food reserves are built through the roles of the central government, local governments, and communities, one of which is implemented through the development of Community Food Barns (Lumbung Pangan Masyarakat/LPM) as an effort to empower communities and strengthen food-related institutions. This study aims to analyze the business feasibility of LPM from both financial and non-financial aspects, as well as to formulate development strategies to support food security. The research method employed is a case study using a descriptive exploratory approach with qualitative and quantitative analyses. Financial analysis uses indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Return on Investment (ROI), while non-financial analysis covers legal, organizational, marketing, and socio-economic aspects. The results show that LPM Ngudi Tani is financially feasible, with an NPV of IDR 476,072,831, an IRR of 52%, a payback period of one year, and an ROI of 36%. From a non-financial perspective, LPM has legal status, a clear organizational structure, an established marketing system, and contributes to stabilizing the supply and prices of rice and unhusked rice, as well as creating employment opportunities. The SWOT analysis places LPM in a growth and development position. The main recommended strategy is strengthening partnerships to increase sales, supported by policy measures, resource optimization, and capacity building of human resources.